Outcome of Immune Thrombocytopenic Purpura In a Tertiary Care Centre (Journal of Chittagong Medical College Teachers' Association, 2020)
Background : The study aimed to demonstrate the pattern of clinical presentations and outcome of Immune Thrombocytopenic Purpura (ITP) in Bangabandhu Sheikh Mujib Medical University (BSMMU) Dhaka.Materials and methods: A retrospective study was conducted by record reviewing and analyzing the data of 103 patients of acute ITP, ageing between 1-16 years, at the Department of Paediatric Haematology and Oncology, Bangabandhu Sheikh Mujib Medical University (BSMMU) Dhaka from June 2017 to December 2019. We reviewed the data regarding age, sex, clinical presentations, history of preceding viral infections, vaccination history, laboratory values, different treatment options used and response to the treatment concerning complete response, partial response and poor responders. Statistical analysis performed by using IBM SPSS statistics version 20.Results: We retrospectively reviewed a total of 103 patients. The median age, at the time of presentation, was 5±3.4 years while the mean age was 4.5±2.9 years. The male to female ratio was  1.28:1. Mean platelet count on presentation was 7 x 109/L (Range: 0-24). Twenty three (22.3%) patients had the history of preceding febrile illness. Bruises, petechiae, epistaxis and hematemesis remained the common presentations. Six (5.8%) patients showed spontaneous recovery while 97 (94%) patients received treatment for ITP. Overall, 71 (68.9%) showed a response after treatment. Sixty-two patients (59.22%) showed loss of response and received treatment again. Among these patients, thirty-four patients (33%) developed chronic disease.Conclusion: Majority of patients presenting to our tertiary care centre had severe acute ITP on presentation.After management and follow-up, almost one third of the patients develop chronic disease hence the incidence of developing chronic disease remained high as compared to the other centers.JCMCTA 2019 ; 30 (2) : 81-85